The use of information and communications technology in the construction sector in Gauteng: A case study of Khuthaza affiliated contractors. - Hlahla, Progress. (My University, 2014)
Information and Communications Technology (ICT) has gained increased use in the construction industry in recent years. ICT brings many benefits to an organisation including improving the way information is sourced, manipulated and utilised to increase the efficiency of business processes and improve a company’s productivity. This research demonstrates that while ICT has a role to play in the construction industry, its exploitation by SMEs in South Africa still needs development as they focus on simpler forms of ICT such as mobile phones and landlines, but not advanced solutions such as Enterprise Resource Planning systems and CAD. Furthermore, one of the major challenges identified in this research is the issue of poor ICT skills and the lack of information on available ICT solutions. The government and the private sector have a role to play in ensuring that requisite ICT skills are developed and improved in the sector.
Keywords: Skills; Small and Medium Construction Enterprises; Information communications technology